Observation of Andreev reflections and Josephson effects in point contacts between conventional and the heavy-fennion superconductor URu₂Si₂ - Naidyuk, Yu.G.; Nowack, A.; Ulbrich, E.; Freimuth, A.; Schlabitz, W.; Yanson, I.K.; Menovsky, A.A. (Физика низких температур, 1995)
We have measured the dV/dI vs. V characteristics of point contacts between the heavy-fermion superconductor URu₂Si₂ and the conventional superconductors Zn and NbTi. Contacts between URu₂Si₂ and Zn behave like a superconductor—normal metal—superconductor junction with a thick normal layer in the heavy-fermion part of the contact and show Andreev-reflection type structures related to both the heavy-fermion and the conventional superconductors. In contrast, contacts between URu₂Si₂ and NbTi become superconducting at low bias currents. The data indicate that proximity induced superconductivity is important for the coupling of the two types of superconductivity. With such contacts we also fabricated a closed-loop setup with two NbTi contacts on a URu₂Si₂ sample, which showed SQUID oscillation in a small magnetic field.